Income inequality and mental illness-related morbidity and resilience: a systematic review and meta-analysis. (July 2017) - Ribeiro, Wagner Silva; Bauer, Annette; Andrade, Mário César Rezende; York-Smith, Marianna; Pan, Pedro Mario; Pingani, Luca; Knapp, Martin; Coutinho, Evandro Silva Freire; Evans-Lacko, Sara
Summary: Background: Studies of the association between income inequality and mental health have shown mixed results, probably due to methodological heterogeneity. By dealing with such heterogeneity through a systematic review and meta-analysis, we examine the association between income inequality, mental health problems, use of mental health services, and resilience (defined as the ability to cope with adversity). Methods: We searched the Global Health, PsychARTICLES, PsycINFO, Social Policy and Practice, Embase and MEDLINE databases up to July 6, 2016, for quantitative studies of the association of income inequality with prevalence or incidence of mental disorders or mental health problems, use of mental health services, and resilience. Eligible studies used standardised instruments at the individual level, and income inequality at the aggregated, contextual, and ecological level. We extracted study characteristics, sampling, exposure, outcomes, statistical modelling, and parameters from articles. Because several studies did not provide enough statistical information to be included in a meta-analysis, we did a narrative synthesis to summarise results with studies categorised as showing either a positive association, mixed results, or no association. The primary outcome in the random-effects meta-analysis was mental health-related morbidity, defined as the prevalence or incidence of any mental health problem. This study is registered with PROSPERO, number CRD42016036377. Findings: Our search identified 15 615 non-duplicate references, of which 113 were deemed potentially relevant and were assessed for eligibility, leading to the inclusion of 27 studies in the qualitative synthesis. Nine articles found a positive association between income inequality and the prevalence or incidence of mental health problems; ten articles found mixed results, with positive association in some subgroups and non-significant or negative association in other subgroups; and eight articles found no association between income inequality and mental health problems. Of the nine articles included in our meta-analysis, one reported a positive association between income inequality and mental health problems, six reported mixed results, and two reported no association. Pooled Cohen's d effect sizes for the association between income inequality and any mental disorder or mental health problems were 0·06 (95% CI 0·01–0·11) for any mental disorder, and 0·12 (0·05–0·20) for depressive disorders. Our meta-regression analysis showed that none of the factors considered (sample size, contextual level at which income inequality was assessed, quality assessment, type of instruments, and individual income as control variable) explained heterogeneity between studies ( I 2 89·3%; p<0·0001). Only one study investigated the association between income inequality and resilience; it found greater income inequality was associated with higher prevalence of depression only among individuals with low income. The only study of the role of income inequality as a determinant of the use of mental health services reported no association. Interpretation: Income inequality negatively affects mental health but the effect sizes are small and there is marked heterogeneity among studies. If this association is causal and growing income inequality does lead to an increase in the prevalence of mental health problems, then its reduction could result in a significant improvement in population wellbeing. Funding: None.